(3GdQSGdI GdehVMIs - (3GdMSjfj, GdeXaQ Hf LYaQ Hf GdMSjf, J b (B14 (3g`s ((3GdeOQSI GdfXGejI HHZOGOs)
(3ChdgG (B:s
(3GdTjYI(B... (3BQGDge heGdJ GdTjYI Edi CejQ GdeDefjf Ydj Hf CHj WGdH(B... (3hGdeNJUjf HCgd HjJ GdfHhI(B...s
(3BNQgG (B:s
(3hGSJYed GddWa ajg, hbd dg bhdG djfG hCONd Ydjg eONdG QajbG dYdg jQLY Yf aXjY ebGdg(B... (3hGdMeO ddg QH GdBNQI hGdChdi(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B893s
(3GdPQjYI, Qbe(B: 1374s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B893s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds